(untitled) - Dr. Chanchal Sachdeva Suri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Studies have revealed in the past that Information shared via Graphic representation impacts more and is retained by humans in a better manner than the information shared merely through words. Infographics is an improvised way of sharing news/information via Media and hence, even the news dailies these days use this medium in large numbers. This research is intended to analyse theInfographics of four national dailies and how these Infographics have been applied to provide information during the national emergency of COVID-19. A total of 58Infographics were published between 11thMarch to 19th March 2020. These infographics were further analysed on the basis of visuals, content and knowledge.